Intra-peritoneal abscess after an abdominal hysterectomy involving Cutibacterium avidum (former Propionibacterium avidum) highly resistant to clindamycin. (October 2019) - Legaria, M.C.; Barberis, C.; Camporro, J.; Traglia, G.M.; Famiglietti, A.; Stecher, D.; Vay, C.A.
Abstract: Cutibacterium avidum is a gram-positive anaerobic rod belonging to the cutaneous group of human bacteria with preferential colonization of sweat glands in moist areas. The microorganism rarely cause disease, generally delayed prosthetic joint infections (PJIs). We describe the second case of intraperitoneal abscess by C. avidum after an abdominal surgery in an obese female patient and the first case after a non-prosthetic abdominal surgery due to a highly clindamycin resistant strain in a patient with underling conditions. The patient was successfully treated with surgical drainage and beta-lactam antibiotics. Although rare and apparently non-pathogenic, C. avidum may be involved in infections, especially in some high-risk patients with obesity who have undergone surgical incision involving deep folder of the skin. The microorganism was identified by phenotypic methods, MALDI-TOF MS and 16S rRNA gene sequencing. Susceptibility test should be performed in C. avidum because high level resistance to clindamycin could be present. We present a literature review of C. avidum infections. Highlights: Intra-peritoneal abscess after an abdominal hysterectomy caused by Cutibacterium avidum highly resistant to clindamycin. The organism was successfully identified by MALDI-TOF MS and confirmed with 16S rRNA gene sequencing. We provided a review of C. avidum infections other than PJIs reported in the literature.